MINE DRAINAGE FACILITY PLANNING ON THE RINJANI WASTEDUMP ON PT XYZ COAL MINE - Mutiara Saumi, Elvira
PT XYZ is an open pit coal mining company with mining operations located in South Kalimantan Province. Rainy conditions will affect the productivity of open pit mines so that a hydrological evaluation is needed and the design of proper drainage facilities to drain the water so as not to interfere with the mining process. This research starts with the analysis of rain data from Rain Measurement Station 2 for the data period 2013-2021 using the Pearson III Log distribution, the rainfall was 118,66 mm with the rainfall intensity in the 10-year return period was 25,91 mm/hour. From the topographic data and the mine plan scheduling data, catchment areas are made. In PT XYZ's Rinjani stockpile, the total catchment area of 3,17 km² is divided into several subcatchments with varying values so that drainage facilities are needed in the form of open channels, drop structures, as well as retention ponds and settling ponds. The open channel is divided into 4 (four) categories which are divided into the first 3 (three) categories for the main trapezoidal channel with dimensions of bottom width x top width x height are : 1 x 3 x 1 m; 1 x 4 x 1,5 m; 1 x 5,6 x 2,3 m. While category 4 is triangular in shape with dimensions of width x height: 3.7 x 1.6 m will be made on the bench. A drop structure is made for 3 (three) steep embankment slopes. 2 (two) retention ponds and 2 (two) settling ponds for the 2020-2023 period and 1 (one) additional retention pond and settling pond for the 2023-2030 period with varying retention pond dimensions and the same settling pond dimensions for each the pool.